2008
DOI: 10.1111/j.1945-5100.2008.tb01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons and amino acids in meteorites and ice samples from LaPaz Icefield, Antarctica

Abstract: Ice samples collected from directly underneath the meteorites were extracted. In addition, exhaust particles from the snowmobiles used during the expedition were collected to investigate possible contributions from this source. The meteorite samples, the particulate matter and solid-state extracts of the ice samples and the exhaust filters were subjected to two-step laser mass spectrometry (L2MS) to investigate the PAH composition. For amino acids analysis, the meteorites were extracted with water and acid hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 43 publications
0
38
1
Order By: Relevance
“…The firn pollution by PAHs was apparently not influenced by snowmobile exhaust, as PHE would be more prominent whereas NAP and M-NAPs would be negligible. [29] …”
Section: Occurrence Of Pahs In Snow Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The firn pollution by PAHs was apparently not influenced by snowmobile exhaust, as PHE would be more prominent whereas NAP and M-NAPs would be negligible. [29] …”
Section: Occurrence Of Pahs In Snow Samplesmentioning
confidence: 99%
“…[28] PAH patterns in ice were also studied in the context of meteorite research although concentrations were not reported (e.g. Botta et al [29] ).…”
Section: Introductionmentioning
confidence: 99%
“…Ice from the Antarctic regions of Allan Hills [143,144] and La Paz [130,147] contained only trace levels of aspartic acid, serine, glycine, alanine, and g-ABA (less than 1 ppb of total amino acid concentration). Ice from the Antarctic regions of Allan Hills [143,144] and La Paz [130,147] contained only trace levels of aspartic acid, serine, glycine, alanine, and g-ABA (less than 1 ppb of total amino acid concentration).…”
Section: Determination Of the Amino Acid Content Of The Meteorite Falmentioning
confidence: 99%
“…Dachs (2014), Sources and fate of polycyclic aromatic hydrocarbons in the Antarctic and Southern Ocean atmosphere, Global Biogeochem. Cycles, 28, 1424-1436, doi:10.1002 to research stations [Cabrerizo et al, 2012;Aislabie et al, 1999;Mazzera et al, 1999], (ii) emissions from research and tourist vessels and accidental spills of fuel, (iii) secondary sources due to volatilization from soils and snow as recently demonstrated for persistent organic pollutants (POPs), such as polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) [Cabrerizo et al, 2013;Galbán-Malagón et al, 2013a, 2013b, and (iv) natural sources of PAHs in Antarctica due to natural losses or seeps of petroleum or coal deposits, meteorites, and biogenic production in soils, sediments, and the water column [Botta et al, 2008;Clemett et al, 1998;Naraoka et al, 2000;Wilcke, 2007;Cabrerizo et al, 2012]. This biogenic production could be related to the degradation of diterpenes from the organic matter pool.…”
Section: Citationmentioning
confidence: 99%